Analysis of Online Coaching Needs in Entrepreneurship Development and Start-up Business Management - Rustiadi, Sonny; Nurulfiqri, Zartikazahra (Journal of Management, 2023)
This study aims to analyze the influence of Entrepreneurial Motivation, Coaching Accessibility, Technology Use, Material Quality, and Learning Methods on Business Sustainability. The method used in this study is multiple linear regression with a sample of 100 respondents consisting of business actors in various sectors. The results of the study indicate that Entrepreneurial Motivation has the strongest and most significant influence on business sustainability (B = 0.593; p = 0.000). In addition, Material Quality also has a significant effect on business sustainability (B = 0.181; p = 0.037). However, the variables Coaching Accessibility, Learning Methods, and Technology Use do not show a significant effect in this model (p> 0.05). Simultaneous tests show that the overall regression model is significant (F = 22.721; Sig. = 0.000), with an R Square value of 0.547, which means that 54.7% of the variation in business sustainability can be explained by the independent variables in this study. In addition, this study recommends further study of other factors that can influence business sustainability, such as access to capital and business network support